Water services law in Malaysia: balancing of social interest - Amin, Naemah (2009)
An efficient, effective and sustainable water services are very crucial for human survival. The Malaysian government has recently restructured its legal and institutional framework of water supply services after realizing that the existing regulatory structure did not work effectively for the water industry. The restructuring process has necessarily involved amendment to the Federal Constitution, introduction of new laws and repealing of some of the existing legislations on the subject of water supply services. This process has been considered as a major legal reform in the country and a realization of a focused, centralized and uniform approach in regulating the water services industry. The paper aims to examine the extent to which the new regulatory and administrative structure of this basic human need would be able to balance various interests of stakeholders in water industry including Federal and state governments, water services operators and consumers. The discussion particularly focuses on analyzing whether the new structure improves protection to consumers in terms of getting quality water and solving the problem of shortage and interruption of water supply and water tariffs which have been major consumers’ complaint in relation to water services. An assessment of these issues will be based on the relevant provisions of the Malaysian National Water Services Commission Act 2006 and the Water Services Industry Act 2006 which are currently the main legislations on water services in Malaysia.